1998
DOI: 10.1073/pnas.95.10.5480
|View full text |Cite
|
Sign up to set email alerts
|

Association-induced folding of globular proteins

Abstract: It has generally been assumed that the aggregation of partially folded intermediates during protein refolding results in the termination of further protein folding. We show here, however, that under some conditions the association of partially folded intermediates can induce additional structure leading to soluble aggregates with many native-like properties. The amount of secondary structure in a monomeric, partially folded intermediate of staphylococcal nuclease was found to double on formation of soluble agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 28 publications
8
64
0
Order By: Relevance
“…Upon aggregation the TTR partially unfolded monomeric species may reacquire structure stabilized by intermolecular interactions. Observations agreeing with this possibility were reported in a study with staphylococcal nuclease, which showed that the amount of secondary structure in a monomeric partially folded intermediate doubled upon formation of soluble aggregates and the propensity to aggregate decreased with increasing structural content of the partially folded intermediate (27).…”
Section: Discussionsupporting
confidence: 69%
“…Upon aggregation the TTR partially unfolded monomeric species may reacquire structure stabilized by intermolecular interactions. Observations agreeing with this possibility were reported in a study with staphylococcal nuclease, which showed that the amount of secondary structure in a monomeric partially folded intermediate doubled upon formation of soluble aggregates and the propensity to aggregate decreased with increasing structural content of the partially folded intermediate (27).…”
Section: Discussionsupporting
confidence: 69%
“…Aggregation or self-association is a characteristic property of partially folded (denatured) proteins (68 -72). It has been shown that in some cases the self-association induces additional structure and stability in the partially folded intermediates (73)(74)(75). Table I shows the far-UV CD parameters of ␣-synuclein determined at different protein concentrations and indicates that the spectrum is not affected by an ϳ170-fold increase in protein concentration, consistent with the lack of self-association up to at least 600 M. Fig.…”
Section: Effect Of Al 3ϩ On the Structural Properties And Aggregationsupporting
confidence: 50%
“…Rigorous analysis of such a system would presumably require fitting data to a polynomial whose order would depend on the number of monomers in the aggregate; an additional vexing problem is the existence of multiple oligomeric states. The unfolding process usually exhibits dependence on the concentration of the monomer as observed with staphylococcal nuclease (61,62). Although analysis of the effect of oligomerization is a tractable problem when describing the unfolding of a dimer or a monomer that goes through a dimeric intermediate, analysis of a higher order polynomial where n is indeterminate poses a significant obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…Guanidine-HCl and urea can promote aggregation in unfolding studies due to the association of an intermediate (59) or the denatured state (60). Partially folded intermediates of staphylococcal nuclease aggregate to form more structured species (61,62); partially folded conformations appear to be intermediates in the formation of most aggregates (59) and can be mistaken for kinetic folding intermediates when they form transiently (63). Rigorous analysis of such a system would presumably require fitting data to a polynomial whose order would depend on the number of monomers in the aggregate; an additional vexing problem is the existence of multiple oligomeric states.…”
Section: Discussionmentioning
confidence: 99%